Effect of Delayed Formalin Fixation on Estrogen and Progesterone Receptors in Breast Cancer - Jingxin Qiu; Swati Kulkarni; Rameela Chandrasekhar; Mark Rees; Kathryn Hyde; Gregory E. Wilding; Dongfeng Tan; Thaer Khoury (2010)
We previously reported that delayed formalin fixation (DFF) has a negative effect on immunohistochemical staining of estrogen receptor (ER), progesterone receptor (PR), and HER2. The primary aim of the study was to determine if DFF affected commonly used clones of the ER and PR differentially. The specific clones evaluated were ER clones 1D5, 6F11, and SP1 and PR clones 16, 1E2, and PgR636. Ten breast cancer cases were dissected and fixed at different times (0, 10, and 30 minutes; 1, 2, 4, and 8 hours; and overnight) and were then stained with anti-ER and anti-PR antibodies. The mean Q score for ER started to decline at 2 to 4 hours for clones 1D5 and 6F11 and at 1 hour for SP1. SP1 was superior to 1D5 at the 8-hour mark (P = .03). The Q score for PR started to decline at 1 hour for clones PgR636 and 16 and 4 to 8 hours for 1E2 (P = .03). Based on our findings, it appears that regardless of the antibody clones evaluated, DFF has a negative effect on hormone receptors.